Hipotireoidismo e linfoma multicêntrico em cadela de 4 anos - Aragão, Luiz Henrique Oliveira (Universidade Federal do Tocantins, 2022)
The present works shows the activities carried out during the mandatory Supervised Curriculum internship, for the conclusion of the Veterinary Medicine course at the Federal University of Northern Tocantins, in Araguaína. The objective is to report the practices carried out in the area of Medical and Surgical Practice of Small Animals. The activities were carried out from September 14th to November 17th, lasting 345 hours and under the guidance of Profª. Dr. Andréa Cintra Bastos Tôrres Passos and supervision of Veterinary Doctor Marcio Thomazo Mota. This report contains a description of the internship location, the activities carried out, the number and casuistry of animals that were followed during this period and the procedures performed. There is also a description of a case report of a 4 years old female dog with hypothyroidism and lymphoma, as well as its clinical signs, case discussion and forms of treatment.